Middle managers: estratégias para sobrevivência em ambientes corporativo mutantes - Bastoni, Marco Antonio (2007)
Master´s degree work which identifies some survival strategies and work maintenance used by the middle management of three corporations installed in Brazil, one of high North-American technology, other of telecommunication based on Portuguese, Spanish and Brazilian investment and the last one a national corporation with family control. The study reaches to context the growing importance of the middle gerency for contemporary organizations, to characterize this group of intermediary workers, delineate and differentiate some of their possible roles and show some their vulnerabilities. After that, it presents ten identified strategies which are a result of the analysis of fifteen managers´ interviews from those companies. While comparing the main identified strategies of the Brazilian professionals, it seems like there are patterns in their answers to changes in their professional environments which are related to the company structure level, to the position they occupy, to their work time inside the company and their networking, both inside and outside the company.